A comprehensive food safety short course (FSSC) improves food safety knowledge, behaviors, attitudes, and skills of Ukrainian participants. Issue 4 (29th August 2020) - Ercan Oruc, Duygu; Pokharel, Siroj; Anantheswaran, Ramaswamy C.; Bucknavage, Martin W.; Gourama, Hassan; Shanina, Olga; Cutter, Catherine N.
Abstract : Abstract: Understanding and enacting standardized food safety practices in a global economy is important. In 2018, a comprehensive food safety training program, including courses in sanitation, food microbiology and mycology, thermal processing, Hazard Analysis and Critical Control Points, cereal quality, and food defense, was delivered to food industry professionals, students, and faculty members in Kyiv, Ukraine. The curriculum included lectures, hands‐on laboratories, as well as case studies and product development activities. Prior to the delivery of the curriculum, demographic data were collected ( n = 33). Participants' food safety knowledge, attitude, behavior, and skills were assessed prior to the program starting and after program completion (immediately and 6 months later). Food safety knowledge of participants immediately after the program and 6 months later was significantly higher ( p < .05) than before the program started. Immediately after the delivery of the curriculum and 6 months later, the participants' food safety attitude and behavior were positively enhanced, with long‐term, sustained changes in proper food safety practices, training requirements, and regulations. Additionally, handwashing skills were improved significantly because of the training program. Use of case studies and product development activities demonstrated positive impacts on participants' food safety learning experience in terms of awareness of their knowledge, communication skills, and the ability to connect scientific concepts and real‐life examples. To our knowledge, little information exists on the use of these training tools with international audiences. This information may be useful to food industry professionals, researchers, and academics who are interested in finding ways to improve the global safety of the food supply through training and education.